Who bears the burden of universal health coverage? An assessment of alternative financing policies using an overlapping-generations general equilibrium model. Issue 7 (18th June 2020) - Abu-Zaineh, Mohammad; Awawda, Sameera; Ventelou, Bruno
Abstract: In their quest for universal health coverage (UHC), many developing countries use alternative financing strategies including general revenues to expand health coverage to the whole population. Unless a policy adjustment is undertaken, future generations may foot the bill of the UHC. This raises the important policy questions of who bears the burden of UHC and whether the UHC-fiscal stance is sustainable in the long term. These two questions are addressed using an overlapping generations model within a general equilibrium (OLG-CGE) framework applied to Palestine. We assess and compare alternative ways of financing the UHC-ridden deficit ( viz . deferred-debt, current and phased-manner finance) and their implications on fiscal sustainability and intergenerational inequalities. The policy instruments examined include direct labour-income tax and indirect consumption taxes as well as health insurance contributions. Results show that in the absence of any policy adjustment, the implementation of UHC would explode the fiscal deficit and debt-GDP ratio. This indicates that the UHC-fiscal stance is rather unsustainable in the long term, thus, calling for a policy adjustment to service the UHC debt. Among the policies we examined, a current rather than deferred-debt finance through consumption taxation emerged to be preferred over other policies in terms of its implications for both fiscal sustainability and intergenerational inequality.